The unglazed pottery of Dvin in the 9th century according to the archaeological works of 2023 - Abrahamyan, Hamazasp (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
In 2022-2023, archaeological investigations were conducted prior to the design work for a new museum facility as part of the museumification and restoration program of the Dvin archaeological site. Three distinct archaeological strata were documented across two excavation areas designated as A and B. The uppermost stratum exhibits a disturbed state and lacks coherent archaeological contexts. The second archaeological stratum represents sedimentary deposits associated with the water supply conduit system that encircled the citadel and traversed the urban settlement. The third and primary archaeological stratum contains well-preserved archaeological contexts, yielding abundant material culture assemblages dated to the 9th century AD. The chronological attribution of this stratum is substantiated by the substantial quantities of glazed ceramics recovered from the primary deposit and dated to the 9th century AD, as well as stratigraphic evidence of destruction debris attributed to the 894 AD seismic event. The majority of unglazed ceramic material recovered from this densely occupied sector of 9thcentury Dvin, while predominantly preserved in fragmentary condition, represents nearly the complete typological repertoire characteristic of 9th-century Dvin ceramics. This paper presents an analysis of the unglazed ceramic assemblage dated to the 9th century AD recovered from the excavations, contextualizing the material within the broader framework of 9thcentury unglazed pottery traditions at Dvin.